Doing school history as portrayed in assessment tasks found in the European expansion and conquest in the 15th to 18th centuries units contained in a sample of grade 10 South African CAPS-compliant history textbooks - Mackenzie, Basil Alexander (My University, 2015)
The aim of this research is to determine what understanding of doing school history is portrayed in assessment tasks in a sample of Grade 10 history textbooks. Bernstein’s pedagogic device provides the framework for an investigation into the nature of history within the fields of production and recontextualisation. Within the field of recontextualisation it is important to understand the purpose of school history as portrayed in curricula and textbooks. The construct of history must be clear to determine whether construct validity exists in history textbook assessment tasks. This construct consists of an academic and political dimension. The analytical lens to determine the construct of history evident in Grade 10 textbook assessment tasks is drawn from Morgan and Henning’s Dimension A and C. The analytical lens for the academic dimension is operationalised through the History CAPS, Bloom’s Revised Taxonomy, and the political dimension through Wertsch’s Table of Collective Memory and History. The finding that emerges from the academic dimension is that the textbook assessment tasks are rigorous in terms of cognitive level spread, and that conceptual knowledge is most often assessed. In the political dimension it is evident that both official (explicitly identifiable in the History CAPS) and unofficial (implied or not identifiable in CAPS) political projects exist.
A research report submitted to the Wits School of Education, Faculty of Humanities, University of the Witwatersrand in partial fulfilment of the requirements for the degree of Master of Education by combination of coursework and research. Johannesburg March 2015